2020
DOI: 10.1021/jacs.0c06767
|View full text |Cite
|
Sign up to set email alerts
|

Unique Hydrogen Bonding of Adenine with the Oxidatively Damaged Base 8-Oxoguanine Enables Specific Recognition and Repair by DNA Glycosylase MutY

Abstract: The DNA glycosylase MutY prevents deleterious mutations resulting from guanine oxidation by recognition and removal of adenine (A) misincorporated opposite 8-oxo-7,8-dihydroguanine (OG). Correct identification of OG:A is crucial to prevent improper and detrimental MutY-mediatedadenine excision from G:A or T:A base pairs. Here we present a structure–activity relationship (SAR) study using analogues of A to probe the basis for OG:A specificity of MutY. We correlate observed in vitro MutY activity on A analogue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…Indeed, Glu188 adopts a different rotamer away from the base that is not completely engaged in the LRC structure ( 39 ) as well as in the N146S-OG:P structure (Figure 4F ). The disengaged base position seen in the LRC and the N146S-OG:P structure described here suggests subtle changes in active site residues alter the proper alignment of the base, which is likely a key quality control mechanism by MutY, and is consistent with previous work that showed reduced activity with structural changes in A ( 35 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, Glu188 adopts a different rotamer away from the base that is not completely engaged in the LRC structure ( 39 ) as well as in the N146S-OG:P structure (Figure 4F ). The disengaged base position seen in the LRC and the N146S-OG:P structure described here suggests subtle changes in active site residues alter the proper alignment of the base, which is likely a key quality control mechanism by MutY, and is consistent with previous work that showed reduced activity with structural changes in A ( 35 ).…”
Section: Resultssupporting
confidence: 90%
“…The purine substrate is structurally similar to adenine except for the lack of exocyclic amino group that alters base-pairing with OG, as well as potential contacts within the MutY active site. Purine has been previously reported to show a higher acid lability than adenine and is excised only ∼2-fold slower than adenine by WT Ec MutY ( 33 , 35 ) with a product release rate of 0.003 ± 0.001 min −1 ( 33 ). In contrast, the rate constants k 2 for purine removal by N146S Gs MutY and N140S Ec MutY revealed a much more dramatic reduction in the activities by ∼92-fold and ∼200-fold in comparison to the respective WT enzymes (Table 1 , Figure 2A&B ).…”
Section: Resultsmentioning
confidence: 99%
“…In the dsDNA chain with a G-A mismatch, the mismatched adenine (A) base is extruded from the double-helix structure of the DNA chain and is bound firmly in the catalytic center pocket of the MutY protein via H-bond interactions with the amino acid residues of MutY, e.g., the N1 of adenine in the DNA chain, the Gln25 residue of MutY, the N7 of adenine, and the carboxyl group of the Glu37 residue/hydroxyl group of the Ser120 residue. At the same time, as for guanine (G), H-bonds are formed between the N1/N2 of guanine in the DNA chain and the Gln42/Thr43 residues, and the Leu80 main chain of the MutY protein. ,, These multiple H-bonds form a strong and stable hydrogen-bond network, enabling the effective binding of the dsDNA chain with the MutY protein.…”
Section: Resultsmentioning
confidence: 99%
“…The Pf HG­(X)­PRT purine binding site is formed by hydrophobic residues (Tyr116, Ile146, Phe197, Val198, and Leu203) . Prior studies have shown that gas-phase data lend insight into the reactivity in the nonpolar environment of enzyme active sites. Specifically, it has been found that if the role of the enzyme is to provide a hydrophobic environment, then ease of reaction depends on the intrinsic lability of the substrate, and the gas-phase acidities and/or proton affinities (depending on mechanism) will track, trendwise, with enzyme rate. We therefore aimed to ascertain whether our gas-phase data could provide insight into the Pf HG­(X)­PRT mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we focus on the properties of HG­(X)­PRT substrates. Prior studies have shown that the examination of properties in the gas phase, which provides the “ultimate” nonpolar environment, uncovers intrinsic, inherent reactivity that correlates to activity in other nonpolar media, including hydrophobic enzyme active sites. In this paper, we calculate and measure the gas-phase acidities and proton affinities (PA) of a series of Pf HG­(X)­PRT purine substrates not heretofore studied in vacuo . We also conduct energetics and kinetic isotope effect (KIE) calculations; all of these results are discussed in the context of the HG­(X)­PRT mechanism.…”
Section: Introductionmentioning
confidence: 99%